Advances in open domain question answering - Strzalkowski, Tomek (Text, speech and language technology, 2008)
Automated question answering - the ability of a machine to answer questions, simple or complex, posed in ordinary human language - is one of today’s most exciting technological developments. It has all the markings of a disruptive technology, one that is poised to displace the existing search methods and establish new standards for user-centered access to information. This book gives a comprehensive and detailed look at the current approaches to automated question answering. The level of presentation is suitable for newcomers to the field as well as for professionals wishing to study this area and/or to build practical QA systems. The book can serve as a "how-to" handbook for IT practitioners and system developers. It can also be used to teach advanced graduate courses in Computer Science, Information Science and related disciplines. The readers will acquire in-depth practical knowledge of this critical new technology. Approaches to question answering -- Some advanced features of cc's poweranswer -- A statistical approach for open domain question answering -- Coreference in q&a -- Question processing -- Questions and intentions -- Question answering as dialogue with data -- Coping with alternate formulations of questions and answers -- Question answering as information retrieval -- Sentence ranking using keywords and meta-keywords -- Question answering by passage selection -- Query modulation for web-based question answering -- Answer extraction -- Question answering by predictive annotation -- Question answering supported by multiple levels of information extraction -- How to select an answer string? -- Evaluating question answering systems -- Evaluating question answering system performance -- Evaluating interactive question answering -- Habitability in question-answering systems -- erspectives on question answering -- Question answering: technology for intelligence analysis -- Reverse-engineering question/answer collections from ordinary text -- New directions in question answering.